REAKSI PASAR SAHAM TERHADAP PENGUMUMAN PERUBAHAN PERINGKAT OBLIGASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Meilia Rakhmawati; Dyah Fitriani (Universitas Ahmad Dahlan, 2012)
Investor decision in buying or selling stocks very influenced by information accepted. Change of obligation rating announcement represent one of new information publicized to public. This research aim to know how the stock market reaction to change of obligation rating announcement for company listed Indonesia stock exchange. Data used by is data of annoucement rating from PT. Pefindo. The population of this research are all companies that announce IDX bond rating in the period 2008-2009. Result of research show in case of decrease of obligation rating is not found by the existence of negativity reaction which significant of during periode test that goes on. WHile for the case of increase of obligation rating not found by the existence of positive reaction significant of during used test period. Inexistence react the market can because of capital market of Indonesia which not yet enough great at manage information circulating so that interpretation for existing information do not yield the correct invesment decision.